Asian Pacific Association of Gastroenterology (APAGE) Inflammatory Bowel Disease (IBD) Working Party guidelines on IBD management during the COVID‐19 pandemic. Issue 3 (5th June 2020) - Ling, Khoon Lin; Hilmi, Ida; Raja Ali, Raja Affendi; Leong, Rupert W L; Leung, Wai Keung; Ng, Siew Chien; Wu, Kai Chun; Chen, Min Hu; Ran, Zhi Hua; Hisamatsu, Tadakazu; Ahuja, Vineet; Makharia, Govind K; et al.
Abstract: The COVID‐19 pandemic, secondary to SARS‐CoV‐2, has resulted in high mortality and morbidity worldwide. As inflammatory bowel disease (IBD) is a chronic disease, and most patients are on long‐term immunosuppressive agents, there is understandable concern, particularly in terms of therapy. In view of this, experts in IBD across the Asia Pacific region were invited to put together recommendations based on their experience and the currently available data. In general, most IBD therapies (with a few exceptions) can be continued safely, and the general consensus is that maintaining disease control should remain the main principle of management. In addition, social distancing measures and the appropriate use of personal protective equipment should be strictly adhered to. During the current pandemic, face‐to‐face clinic follow ups and non‐urgent procedures should be kept to a minimum. Abstract : This is a concerted effort by the members of the Asian Pacific Association of Gastroenterology Inflammatory Bowel Disease (IBD) Workgroup members to provide guidance on IBD management (all‐in‐one succinct review paper) during the difficult COVID‐19 pandemic.